THE GEOGRAPHIES OF REMINISCENCE: MEMORY, LITERATURE, AND EXILE (Andamios, Revista de Investigación Social, 2011)
Summary: During the last thirty years, a memory culture, developed in multiple artistic, political and social manifestations, has been consolidated. The rise of particular memories, which are dispersed, broken up and in conflict (from which the foundations of national projects are questioned) is a symptom of this change that affects societies in relation to the experience of temporality. In the literary practicing this change has produced a certain type of literature that works with the past to recover particular memories. It is in this perspective that I propose the analysis of Las genealogías by Margo Glanz and Los rojos de ultramar by Jordi Soler.
Keywords: Memory; exile; literature; Glanz; Soler